Improvement of Soccer Dribbling Learning Results Through Play Approaches - Zulfikri, Zulfikri (Jurnal Primagraha, 2021)
In general, the purpose of this study was to improve the learning outcomes of soccer dribbling in physical education learning by using a playing approach for Grade VII students of MTs Muhammadiyah 3. The scope of this study used an action research approach. The subjects in this study were Grade VII students of MTs Muhammadiyah 3 Kisaran. This research was conducted at MTs. Muhammadiyah 3 ranges. The frequency of the research is two meetings in one cycle, where one meeting is once a week according to the physical education class schedule at school. the result is that the average student score in football dribbling learning is 69.2 or 57.% or 17 students who complete, and 43% of students who do not complete or total 13 students who do not complete in cycle I. In cycle II which is realized through action the reflection results of cycle I, the result is an average student score of 76.4 or 86.67% with the number of students who complete 26 students complete and 13.33% students who do not complete or 4 students who do not complete. Based on the results of the study it can be concluded that: (1) The approach to playing the results of learning dribbling football increases, (2) The approach to playing which is applied through the game helps students in improving the learning outcomes of dribbling football.